Bispidines for radiopharmaceuticals - Comba, Peter; Kerscher, Marion; Rück, Katharina; Starke, Miriam (Dalton transactions, 2018)
Very rigid tetra-, penta-, hexa-, hepta- and octadentate bispidine ligands are well preorganized for specific coordination geometries. The broad range of coordination numbers, geometries and donor sets allows one to design and prepare bispidines for many specific metal ions and applications. Major requirements for radiopharmaceuticals are efficient labeling, inertness under physiological conditions and easy functionalization of the ligands with biological vectors. The reasons why bispidines are among the most favorable chelators for radiopharmaceutical applications, a comprehensive list of bispidine ligands and a range of examples where bispidines have been used to develop radiopharmaceuticals for future applications in diagnosis and therapy are discussed.